Longitudinal Profiles of Metabolism and Bioenergetics Associated with Innate Immune Hormonal Inflammatory Responses and Amino‐Acid Kinetics in Severe Sepsis and Systemic Inflammatory Response Syndrome in Children. Issue 6 (16th January 2018) - Spanaki, Anna Maria; Tavladaki, Theonymfi; Dimitriou, Helen; Kozlov, Andrey V.; Duvigneau, J. Catharina; Meleti, Eftychia; Weidinger, Adelheid; Papakonstantinou, Evangelos; Briassoulis, George
Abstract: Background: Experimental data indicate that sepsis influences the mitochondrial function and metabolism. We aim to investigate longitudinal bioenergetic, metabolic, hormonal, amino‐acid, and innate immunity changes in children with sepsis. Methods: Sixty‐eight children (sepsis, 18; systemic inflammatory response syndrome [SIRS], 23; healthy controls, 27) were enrolled. Plasma amino acids were determined by high‐performance liquid chromatography (HPLC); flow‐cytometry expressed as mean fluorescence intensity (MFI) of heat shock protein (HSP) levels from monocytes (m) and neutrophils (n); resistin, adiponectin, and extracellular (e) HSPs evaluated by ELISA; ATP levels in white blood cells by luciferase luminescent assay; lipid peroxidation products (TBARS) by colorimetric test; nitrite and nitrate levels by chemiluminescent assay; biliverdin reductase (BVR) activity by enzymatic assay; and energy‐expenditure (EE) by E‐COVX. Results: Resistin, eHSP72, eHSP90α, and nitrate were longitudinally higher in sepsis compared with SIRS ( p <0.05); mHSP72, nHSP72, VO2, VCO2, EE, and metabolic pattern were repressed in sepsis compared with SIRS ( p <0.05). Septic patients had lower ATP and TBARS compared with controls on day 1, lower ATP compared with SIRS on day 3 ( p <0.05), but higher levels of BVR activity. Sepsis exhibited higher phenylalanine levels on day 1, serine on day 3; lower glutamine concentrations on days 3 and 5 ( p <0.05). Resistin, inversely related to ATP, was independently associated with sepsis, along with mHSP72 and eHSP90α ( p <0.05); TBARS and VO2 were independently associated with organ failure ( p <0.05)). Septic nonsurvivors had malnutrition, persistently repressed metabolism, mHSP72, and induced resistin and adiponectin ( p <0.05). Conclusions: A pattern of early longitudinal induction of metabolic‐hormones and eHSP72/HSP90α, repression of bioenergetics and innate immunity, hypo‐metabolism, and amino‐acid kinetics changes discriminate sepsis from SIRS; malnutrition, hypo‐metabolism, and persistently increased resistin and adiponectin are associated with poor outcome.